2020
DOI: 10.1021/acs.joc.0c00783
|View full text |Cite
|
Sign up to set email alerts
|

Tri- and Tetrameric Proanthocyanidins with Dentin Bioactivities from Pinus massoniana

Abstract: Guided by dentin biomechanical bioactivity, this phytochemical study led to the elucidation of an extended set of structurally demanding proanthocyanidins (PACs). Unambiguous structure determination involved detailed spectroscopic and chemical characterization of four A-type dimers (2 and 4−6), seven trimers (10−16), and six tetramers (17−22). New outcomes confirm the feasibility of determining the absolute configuration of the catechol monomers in oligomeric PACs by one-dimensional (1D) and two-dimensional (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 33 publications
(166 reference statements)
3
33
0
Order By: Relevance
“…The two 4β→6 linkages were deduced from the chemical shifts of C-6 (δ C 110.5 in the G-ring and δ C 111.0 in the M-ring) and ECD evidence. Units II and IV were both elucidated as epicatechin by the singlet signals of II-H-2 and IV-H-2 and the upfield shifted C-2 (δ C 78.7 in F-ring and δ C 79.9 in the L-ring) to the corresponding carbon in proanthocyanidin A1 ( 4 ) (δ C 81.6) . Phloroglucinolysis confirmed the absolute stereochemical assignments.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…The two 4β→6 linkages were deduced from the chemical shifts of C-6 (δ C 110.5 in the G-ring and δ C 111.0 in the M-ring) and ECD evidence. Units II and IV were both elucidated as epicatechin by the singlet signals of II-H-2 and IV-H-2 and the upfield shifted C-2 (δ C 78.7 in F-ring and δ C 79.9 in the L-ring) to the corresponding carbon in proanthocyanidin A1 ( 4 ) (δ C 81.6) . Phloroglucinolysis confirmed the absolute stereochemical assignments.…”
supporting
confidence: 87%
“…A NOESY correlation between II-H-3 and III-H-6 indicated a 3,4- trans configuration in the F-ring, and thus II-C-3 was S-configured . A comparison of the tendency of ECD curves of 1 in the diagnostic region 280–300 nm with those of proanthocyanidin A2 ( 5 ) and proanthocyanidin A5 ( 7 ) revealed that 1 is closely mirror-symmetric to 7 (Figure B). Thus the partial structures of units II and III in 1 were assigned to be enantiomeric to those in 7 .…”
mentioning
confidence: 99%
See 3 more Smart Citations